SOCIOLOGY OF CULTURE - Perrin, Andrew (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Goals1. To survey the literature in the sociology of culture, with an emphasis on current approaches to culture2. To stimulate ideas for empirical work in cultural sociology3. To offer cultural tools for application to empirical research